TEENAGER RELATIONSHIP IN NICOLA YOON’S NOVEL EVERYTHING, EVERYTHING - Nurtia Pratiwi Siahaan; Sri Wulan (JOURNAL OF LANGUAGE, 2020)
This study was conducted to give an overview to all people about the portrayal of teenager relationship and its negative impact in the novel. This study applies  qualitative method which collects the data taken from the novel that have been read. The result shows that the relationship in the novel is portrayed as an unhealthy relationship. It is described as if it were an adult relationship. Their relationship is too romantic and too intimate. Such relationship is, of course, not suitable for their age as the protagonist and her lover are still teenagers. Consequently, the relationship result in negative impacts. The negative impacts which can be found in the novel are opposition, carelessness, and lying. These impacts happen to the protagonist after she has the love relationship. On the basis of the result of this study, it can be concluded that having an unhealthy relationship during adolescence may cause a negative impact on themselves and family.